Precipitation is the key determinant of topsoil δ15N values in southern Patagonia’s semiarid rangelands - Peri, Pablo Luis; Duarte Guardia, Sandra; Amelung, Wulf; Ladd, Brenton (American Society of Agronomy, Crop Science Society of America, and Soil Science Society of America, 2022)
Nitrogen (N) cycling in rangeland soils could potentially be controlled by water supply, stocking rates, or a range of other variables, such as ecosystem N stocks. To gauge the relative importance and elucidate possible interactions among these factors, we measured many abiotic variables to identify first-order controls of δ15N for Patagonia’s rangeland soils under contrasting historical grazing intensities. The results showed that δ15N values declined as water availability increased. The effects of precipitation and stocking rate on soil δ15N values were additive, and the effect of precipitation far outweighed the effects of grazing pressure. The soil N stock was a weak predictive variable for modeling variation in δ15N of the soil. Earlier assumptions about an inflection point for N cycling and δ15N values related to aridity were not confirmed. We conclude that variation in water availability drives variation in δ15N values irrespective of grazing intensity. We also conclude that meaningful interpretation of δ15N in soil will require a better mechanistic understanding of the interactions between water and N in the vadose zone than we currently possess.